Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-03-03T22:26:24+01:00
Salut,

A = 3 - (2t + 3)
A = 3-2t - 3
A = -2t

B = 5t + (-3t + 5)
B = 5t -3t + 5
B = 2t + 5

C = 5+(5-6t)
C = 5 + 5 - 6t
C = 10 - 6t

D = 2 - (-2t +9)
D = 2 + 2t -9
D = -7 + 2t

E = 3t + (-6t +12)
E = 3t - 6t + 12
E = -3t + 12

F = -6t - (-9t - 11)
F = -6t + 9t + 11
F = 3t +11

Bonne soirée !
  • Utilisateur Brainly
2014-03-03T22:29:39+01:00
N° 21:

A= 3 - ( 2t + 3)
A= 3 - 2t - 3
A= -2t

B= 5t + (-3t + 5)
B= 5t -3t + 5
B= 2t + 5

C= 5 + (5-6t)
C= 5 + 5 -6t
C= -6t + 10

D= 2 - (-2t + 9)
D= 2 + 2t -9
D= 2t -7

E= 3t + (-6t + 12)
E= 3t -6t +12
E= -3t + 12

F= -6t - (-9t - 11)
F= -6t + 9t + 11
F= 3t +11

Voilà ! :)